2014
DOI: 10.1111/bcp.12227
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 variation, behaviour and psychopathology: implications for pharmacogenomics‐guided clinical trials

Abstract: Individual and population differences in polymorphic cytochrome P450 enzyme function have been known for decades. The biological significance of these differences has now been deciphered with regard to drug metabolism, action and toxicity as well as disposition of endogenous substrates, including neuroactive compounds. While the cytochrome P450 enzymes occur abundantly in the liver, they are expressed in most tissues of the body, albeit in varying amounts, including the brain. The latter location of cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…The physiological role of CYP2D6 is not well defined as few high-affinity endogenous substrates have been identified. CYP2D6 is responsible for O-demethylation of pinoline[37] and of 6-methoxytryptamine to serotonin[38], which may account for the well-established association between CYP2D6 activity and personality[39,40]. It is unlikely, though possible, that these physiological differences are related to prognosis of ER+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of CYP2D6 is not well defined as few high-affinity endogenous substrates have been identified. CYP2D6 is responsible for O-demethylation of pinoline[37] and of 6-methoxytryptamine to serotonin[38], which may account for the well-established association between CYP2D6 activity and personality[39,40]. It is unlikely, though possible, that these physiological differences are related to prognosis of ER+ breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]20,21 However, an important limiting factor of the present study is the lack of data about the individuals' drug treatment and their drug plasma levels. As most of the available information about these polymorphic genes is related to drug therapeutic failure, the independent relationship between CYP2D6 and CYP2C19 with suicide severity could be expected in the individuals taking drug metabolized by these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Thus, the effect of CYP2D6 on suicidal behavior can be partially due to drug therapeutic failure during treatment with CYP2D6 substrates and/or to differences in the CNS regulation. In support of the latter hypothesis, variability in CYP2D6 has been linked to differences in personality traits, neurocognitive functions and mental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the recent discovery of a high CYP2D6 hydroxylation capacity by the presence of -1584G allele in the promoter region of the CYP2D6 gene [22] emphasizes the need of an improvement in the genetic analysis in order to take into account other factors apart from gen duplication/multiplication. The effect of UM for CYP2D6 on suicidal behavior has to be highlighted since several studies have found poor response to antidepressant drugs or early dropout from monotherapy treatment with CYP2D6 antidepressant substrates [23,24].…”
Section: Pharmacogenetics and Personalized Therapeutics Networking Lmentioning
confidence: 99%